2020
DOI: 10.3390/agriculture10120608
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Plant Growth and Physiological Responses to Soil Salinity during Tillering and Stalk Elongation

Abstract: A pot study was conducted to investigate influences of salinity on sugarcane (Saccharum spp.) plant growth, leaf photosynthesis, and other physiological traits during tillering and stalk elongation. Treatments included two commercial sugarcane cultivars (Canal Point (CP) 96-1252 and CP 00-1101) and an Erianthus with five different soil salt concentrations (0 [Control], 38, 75, 150, and 300 mM of NaCl added). Growth (tillers, plant height, and nodes) and physiological (leaf net photosynthetic rate [Pn], stomata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Additionally, the decrease in stomatal conductance and subsequent stomatal closure leads to a decrease in active photosynthesis and stem height. According to our ndings, (Zhao et al, 2020) also reported a decrease in active photosynthesis in sugarcane due to salinity stress, attributed to a decrease in stomatal conductance and photosynthetic factors in the leaves. Additionally, Vasantha et al…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, the decrease in stomatal conductance and subsequent stomatal closure leads to a decrease in active photosynthesis and stem height. According to our ndings, (Zhao et al, 2020) also reported a decrease in active photosynthesis in sugarcane due to salinity stress, attributed to a decrease in stomatal conductance and photosynthetic factors in the leaves. Additionally, Vasantha et al…”
Section: Discussionsupporting
confidence: 54%
“…The length of milling stalks is one of the characteristics that can indicate the tolerance of sugarcane to drought stress, in addition to having a wide heritability, so it can be used as a selection criterion in breeding programs (Hartati and Yuniyati, 2022). In addition to the genotype factor, the significant differences found in stem height may be related to the climatic conditions and soil characteristics in the area where the study was conducted since the driest period coincides with the formative phase of sugarcane, a limiting factor for the normal development of the hybrids (Zhao et al, 2020). The largest stem diameter was found in the hybrid COLPOSCCMex 09-289, with 36.43 mm, and COLPOSCCMex 09-208, with 35.17 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The results can be explained by the fact that, by increasing the salt concentration in the soil, a reduction in the osmotic potential occurs; therefore, the plant is unable to absorb water due to the reduction in the water potential of the soil (Zahra et al, 2020). Zhao et al (2020), when evaluating sugarcane growth under salinity of irrigation water during tillering and elongation, found reductions in plant height of 13.5, 11.1, 18.3, and 31%, respectively, for saline levels of 38, 75, 150, and 300 mM. In addition, Lira et al (2018) evaluated the growth of sugarcane irrigated with brackish water and leaching fractions and found that salinity negatively affected plant stature.…”
Section: Resultsmentioning
confidence: 99%